Towards resilient, responsive and rewarding mining: An adaptive value chains approach. (December 2021) - Lim-Camacho, Lilly; Jeanneret, Talia; Hodgkinson, Jane H.
Abstract: In order to deliver the vital materials needed for a low-carbon economy, the mining chain's resilience to climate impacts must be improved. Management decisions spanning a broad domain need an approach that will support resilience to climate impacts as extremes become more intense. We explore a whole-of-chain approach that considers product flow (the supply chain) and the decisions that influence value created (the value chain). Using a Climate Impacts Framework (the Framework), we generate a qualitative model of the coal value chain in Queensland, Australia, using a cyclone in 2017 as a case study to demonstrate the danger and difficulty of mining and delivering products under an extreme climatic event. The model defines relationships and linkages between impacts occurring at different stages of the chain, indicating interdependencies and influence. Our results highlight the importance of systems perspectives for identifying levers that managers and policy makers can use to facilitate discussion and decision making towards the goal of responsive, resilient and rewarding mining value chains. Highlights: We map the Queensland coal value chain and apply our Climate Impacts Framework. We demonstrate the complexity of impacts of extreme-events on a mining chain. The approach enhances line-of-sight across multiple management decision domains. Resilience may be improved through enriched connections in the value chain.